Antioxidant and Free Radical Scavenging Potential of Otostegia limbata - AHMED, DILDAR; ADIL ARSHAD, MUHAMMAD; NADEEM ASGHAR, MUHAMMAD; IKRAM AUJLA, MUHAMMD (Asian Journal of Chemistry, 2010)
Otostegia limbata is a medicinal herb of family Lamiaceae and is known for its medicinal activities for various ailments. In view of the possibility that some of these activities may be related to the antioxidant compounds found in the plant, we carried out comprehensive antioxidant studies on extracts of the leaves of the plant in water, n-hexane, chloroform, ethyl acetate, n-butanol and methanol. Some extracts showed strong antioxidant activity. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity was determined and EC50 (μg) values were found to be in between 61 (ethyl acetate fraction) and 96 (n-butanol fraction). The total phenolic content varied from 489-1273 mg GAE/100 g, total flavonoid content was 198-3018 mg QE/100 g, TEAC (trolox equivalent antioxidant capacity) values ranged from 30-139 (μmol/g) using ABTS assay, while FRAP (ferric reducing antioxidant power) values ranged from 5-41 (mmol/g). The results of these studies suggest that Otostegia limbata could serve as a source of natural antioxidants with potential applications in food and pharmaceutical industries.